Diversidade linguística brasileira, as línguas páno e suas características ergativas - Abreu, Paulo Sérgio Reis de (2008)
This work focuses on Brazilian linguistic diversity and, within it, the Páno family, from which was pointed out, under the grammatical point of view, the operation of the case systems. The study consists of an introduction, three chapters, a conclusion, bibliography and three appendices. Chapter 1 brings historical information on the linguistic diversity in Brazil at the time of the Portuguese incursion, the present situation of our languages, the methods for linguistic classification and its application on the Brazilian indigenous languages, and also aims at pointing out the importance of the descriptive linguistic studies of our autochthonous languages. Chapter 2 deals specifically with the Páno family, with the history of how the region where it is situated in South-West Amazonia was populated, with the various Páno people situated in Brazil, with classificatory efforts, with studies already carried out by Brazilian researchers, and also searches for establishing a vision of the genetic relationships between those different languages. The chapter 3 brings theoretical information on the study of ergativity, based on Dixon (1994), as well as an analysis of this grammatical phenomenon carried out by Lyons (1968). Afterwards, still in the chapter 3, the case systems from ten Páno languages are summarily observed, as well as the split in the case marking system in some of these languages. The appendices contain: 1) maps of the Amazon region and of the State of Acre, Brazil; 2) symbols of the International Phonetic Alphabet; 3) a updated survey, based on Rodrigues (1986/1994), (1997) and (2005), of all indigenous languages still spoken in Brazil (organized into linguistic families and stocks), number of speakers, location and index of languages.